Developing Critical Thinking Skills in Language Teaching: Oral Interpretation Class - Junining, Esti (Sebelas Maret University, 2016)
Critical Thinking Skill (CTS) is one of the skills that is required to survive in this globalization era. Peopleneed this skill to innovate in technology to increase education quality and to produce outstanding humanresources. However, not many Indonesian learners master this kind of skill. There are still some constraints in applying this skill into action. Both teachers and students have difficulties in implementing this skill in the classroom. This paper aims at producing innovative CTS strategies that are easily conducted in language teaching. The language teaching in this paper is specified in teaching oral interpretation class in which the students are expected to be able to apply CTS to master both receptive skills, listening and understanding audio visual teaching media, and productive skills, producing appropriate oral interpretation skills to bridge the gap between two languages. Constructing questions while watching audio-visual media and taking notes to supplement short term memory is the first innovation in CTS teaching. The second one is taking the essential notes using signs, symbols and figures to get the essence of the source language. Demonstrating a role play in oral interpretation is the final activity in this teaching and learning process.